Deductive Reasoning of Student Teacher Candidates: A Study of Number Theory - Widadah, Soffil; Juniati, Dwi; Khabibah, Siti (JME (Journal of Mathematics Education), 2022)
Deductive reasoning which includes generalizing, justifying, exemplifying, comparing, and classifying is the main feature of studying mathematics. This study aims to describe qualitatively the deductive reasoning of second-semester mathematics teacher candidates in studying number theory. Mathematics teacher candidates who have equal mathematical abilities and are of the same sex, namely women as research subjects. Â The results showed that the two subjects met the indicators of deductive reasoning, namely making general statements, making special statements, and concluding. Â This could be caused by the characteristics of prospective teacher students in receiving, storing, processing, and how to solve problems or what is called cognitive style